2021
DOI: 10.1038/s41467-021-23383-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic manipulation of droplets using mechanically tunable microtextured chemical gradients

Abstract: Materials and strategies applicable to the dynamic transport of microdroplets are relevant to surface fluidics, self-cleaning materials, thermal management systems, and analytical devices. Techniques based on electrowetting, topographic micropatterns, and thermal/chemical gradients have advanced considerably, but dynamic microdroplet transport remains a challenge. This manuscript reports the fabrication of mechano-tunable, microtextured chemical gradients on elastomer films and their use in controlled microdro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…We previously demonstrated that the droplet transport properties (e.g., velocity) of microtextured chemical gradients (mechanically analogous to the gradient surfaces studied here) were unaffected by repeated cycles of stress (up to 100 cycles between ε c = 0 and ε c = 0.2). [ 10 ] We expected comparable mechanical durability in this work and indeed did not observe performance degradation throughout our tests, which typically included several stress cycles. Further, we did not observe residual liquid (in the form of microdroplets or films) using our optical tensiometer (which has an imaging resolution of ≈10 μm).…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…We previously demonstrated that the droplet transport properties (e.g., velocity) of microtextured chemical gradients (mechanically analogous to the gradient surfaces studied here) were unaffected by repeated cycles of stress (up to 100 cycles between ε c = 0 and ε c = 0.2). [ 10 ] We expected comparable mechanical durability in this work and indeed did not observe performance degradation throughout our tests, which typically included several stress cycles. Further, we did not observe residual liquid (in the form of microdroplets or films) using our optical tensiometer (which has an imaging resolution of ≈10 μm).…”
Section: Resultsmentioning
confidence: 66%
“…We previously reported data from confocal microscopy which gives wrinkle characteristics (e.g., amplitude) and surface roughness that agree with theoretical predications made using physical models of mechano‐induced wrinkles. [ 10 ] In these experiments the gradient orientation was always along the propagation axis of the wrinkled microtexture. The fundamental equation (Equation 1) that describes the spontaneous transport of droplets on surface energy gradients predict a critical radius ( R c ) associated with the condition where droplet transport ceases (i.e., velocity, v = 0 and F = 0).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations